Using cardiorespiratory fitness to operationalize vitality: a path analysis on the hierarchical structure of intrinsic capacity - Ruby Yu; Derek Lai; Grace Leung; Cecilia Tong; Jean Woo (Elsevier, 2024)
Background: There is a lack of consensus about the operationalization of vitality, which is one of the intrinsic capacity (IC) domains. In particular, no study has investigated whether cardiorespiratory fitness (CRF) can be considered a vitality indicator. Objective: To examine whether vitality is the upstream domain of IC, and establish the validity of CRF as a vitality indicator, using maximal oxygen consumption (VO2 max) as a representative. Methods: 561 older adults from a longitudinal cohort study were included. Variables under consideration were VO2 max, other IC domains, instrumental activities of daily living (IADL), and handgrip strength, which was considered an already validated indicator of vitality. Using handgrip strength as the reference point, path analyses were performed to examine whether VO2 max followed a similar hierarchical structure in predicting change in IADL difficulty through other IC domains. Results: The mean age of the participants was 75.5 years. The path model in which vitality was measured by VO2 max demonstrated adequate fit, which was similar to the model in which vitality was measured by handgrip strength. Regarding the path coefficients, the model using VO2 max demonstrated significant total and indirect effects. Notably, the indirect effect was due to the locomotor domain (standardized coefficient = −0.148, p < .001), but not the cognitive or psychological domain. Conclusion: Vitality is the upstream domain of IC. VO2 max can be considered an indicator to operationalize the vitality concept.